Immunology of the Antiphospholipid Syndrome: Antibodies, Antigens, and Autoimmune Response - Roubey, Robert A. S. (Thrombosis and Haemostasis, 1999)
The antiphospholipid syndrome (APS) is an autoimmune condition in which a group of autoantibodies are thought to play a direct role in the pathogenesis of thrombosis, fetal loss, and other clinical manifestations. This review will focus on the nature of these autoantibodies, the antigens they recognize, and mechanisms that may contribute to autoimmunity and the production of autoantibodies in patients with APS.